(untitled) (Revista Brasileira Multidisciplinar, 2025)
Changes in food consumption and lifestyle have led to an increase in chronic non-communicable diseases among young individuals. The development of obesity in childhood is worrying, as it is at this stage that lifestyle habits are formed. To reduce excess weight in children, the definition, development and support of interventions aimed at promoting healthy eating through health education are of paramount importance. Therefore, this study aimed to validate a comic book (comic) to promote healthy eating in terms of language, content and appearance of the material according to experts in the field. The research was of the methodological type of validation of educational material, carried out between October/2020 and January/2021. The selection of experts was carried out using research on the Lattes Platform and the snowball method; sent an invitation letter, the HQ and an online form. The statistical analyzes performed were: descriptive, Content Validity Index (CVI), average percentage of material adequacy, Cronbach’s Alpha and Intraclass Correlation Coefficient (ICC). The study was approved by the Research Ethics Committee of the Federal University of Piauí. The comic was evaluated by 21 judges, the majority of whom were nurses and nutritionists. The material was considered adequate, reaching CVI above 0.96, with reliability (Cronbach’s Alpha greater than 0.960) and high response agreement (ICC greater than 0.950) and adequacy percentage equal to 67.7%. The judges considered the comic to be appropriate and with reliable and truthful content.